Pediatric Rare Case of Supracardiac Total Anomalous Pulmonary Venous - Faradilla Novita Anggreini; Pande Putu Yuli Anandasari; Ni Nyoman Margiani; Eka Gunawijaya (Indonesian Journal of Global Health Research, 2024)
Total anomalous pulmonary venous return (TAPVR) is a rare congenital heart defect, and patients are usually symptomatic at a very young age. Survival to adulthood without surgical correction is extremely rare. Objective: presented pediatric rare case of supracardiac total anomalous pulmonary venous. Methods: This study was a case report that describing detailed account of a patient's diagnosis, treatment, and follow-up a rare case. This study presents a single case. Results: we present a rare case of a 2-month-old infant diagnosed with Supracardiac TAPVR accompanied by an Atrial Septal Defect (ASD). The condition was identified through a combination of echocardiography and cardiac CT imaging. In these conditions, a right-to-left shunt is necessary for survival, along with the need for prompt corrective surgery. TAPVR is often associated with heterotaxy syndrome and other congenital heart defects. Various cross-sectional imaging modalities are valuable in detecting and evaluating pulmonary venous development anomalies. Conclution: These modalities provide both anatomical and functional information. Early detection and diagnosis lead to the best management strategies for patients with TAPVR. Multidetector Computed Tomography (MDCT) is a non-invasive imaging technique that plays an increasingly important role in evaluating these anomalies.